Influence of Public Health Services on the Goal of Ending Tuberculosis: Evidence From Panel Data in China - Yang Chen; Yang Chen; Yang Chen; Qingyu Zhou; Qingyu Zhou; Qingyu Zhou; Xinmei Yang; Xinmei Yang; Xinmei Yang; Peiwu Shi; Peiwu Shi; Qunhong Shen; et al. (Frontiers Media S.A., 2022)
BackgroundThe World Health Organization has proposed an initiative to "end tuberculosis (TB)." Unfortunately, TB continues to endanger the health of people worldwide. We investigated the impact of public health services (PHS) in China on TB incidence. In this way, we provided policy ideas for preventing the TB epidemic.MethodsWe used the "New Public Management Theory" to develop two indicators to quantify policy documents: multisector participation (MP) and the Assessable Public Health Service Coverage Rate (ASCR). The panel data from 31 provinces in Chinese mainland were collected from 2005 to 2019 based on 1,129 policy documents and the China Statistical Yearbook. A fixed-effect model was used to determine the impact of MP and the ASCR on TB incidence.ResultsFrom 2005 to 2019, the average MP increased from 89.25 to 97.70%, and the average ASCR increased from 53.97 to 78.40% in Chinese mainland. However, the development of ASCR between regions was not balanced, and the average level in the western region was lower than that in the eastern coastal provinces. With an increase in MP and the ASCR, the TB incidence had been decreasing gradually in recent years. The panel analysis results showed that MP (β = −0.76, p < 0.05). and ASCR (β = −0.40, p < 0.01) had a negative effect on TB incidence, respectively. Even if the control variables were added, the negative effects of MP (β = −0.86, p < 0.05) and ASCR (β = −0.35, p < 0.01) were still statistically significant.ConclusionsPromoting the participation of multiple departments, as well as emphasizing the quality of PHS delivery, are important ways to alleviate the TB epidemic. The settings of evaluation indices for PHS provision should be strengthened in the future.